Louella and the yellow balloon - Coxe, Molly (New York : Crowell, 1988)
Patricia Pig takes her baby, Louella, to the circus and loses her when Louella wanders off to retrieve her new balloon.
13 18
Keywords: Balloons -- Fiction; Pigs -- Fiction; Circus -- Fiction; Animals -- Fiction